Global trends and hotspots of adolescent eating disorders: a bibliometric study and visual analysis - Ye, Qian; Yang, Yiling; Qi, Yue; Li, Jiale; Lei, Huijuan; Sun, Lina; Zhang, Jie (Frontiers in Psychiatry, 2025)
BackgroundAdolescent eating disorders represent a category of mental illness, marked by elevated mortality and morbidity rates and a significant adverse impact on the quality of life of both patients and their families. As one of the most important directions in eating disorders, adolescent eating disorders have significant research value, social value, and practical significance. Surprisingly, the overall research landscape in this domain has yet to be systematically explored through bibliometric analysis. Consequently, this study aims to employ bibliometric methods to analyze published literature, providing a comprehensive and systematic summary of the current research advancements and hotspots in the field of adolescent eating disorders, as well as to forecast potential research directions and future trends.MethodsWe retrieved studies related to adolescent eating disorders from the Web of Science Core Collection database, covering the period from January 1, 2011, to December 31, 2024. We conducted a bibliometric analysis of the literature, employed the visualization tools CiteSpace and VoSviewer. Our study focused on the number of publications, countries, institutions, journals that have cited the works, references, authors, and keywords, to uncover patterns and trends in the field.ResultsA total of 1,077 articles were retrieved. The number of publications in this field has shown a steady upward trend. The United States leads in adolescent eating disorder research. The University of California is the most productive institution, with 134 papers. The International Journal of Eating Disorders is the most cited journal, with 993 citations. The reference “American Psychiatric Association, Diagnostic and Statistical Manual, 5th” has the highest citation frequency. Le Grange Daniel is the most prolific author. High-frequency keywords include “prevalence”, “weight”, and “risk factors”. Emerging keywords are “mental health”, “emotion management”, “social media”, and “validation”.ConclusionsAdolescent eating disorders are gaining increasing global attention. Presently, research on this issue focuses on comorbidities between adolescent eating disorders and other mental illnesses, and their etiology, risk factors, and clinical assessment. In the future, the core research directions in this field will center on verifying the long-term effectiveness of eating disorder treatments, refining personalized assessment and treatment models, and furthering interdisciplinary integration in interventional approaches.